Analisis Struktur Pasar Cabai Rawit Merah (Studi Kasus Pasar Perumnas Way Halim, Bandar Lampung) - Tri Marinda, Siti; Budi Trisnanto, Teguh; Fitriani, Fitriani; Sutarni, Sutarni (Politeknik Negeri Lampung, 2024)
Perumnas Way Halim Market is the first Indonesian National Standard market in Lampung Province. Market analysis was carried out to find business opportunities and potential that could be exploited, in terms of products sold or market structure. Red cayenne pepper has potential because it is a product that is unique that follows trends and high product demand. However, the obstacles faced by this product are fluctuating prices and product supplies being influenced by the weather. This research aimed to analyze marketing channels and market share, market structure, and market structure efficiency. This research used a non-probability sampling approach with the judgmental sampling method. The analysis method consists of four indicators; they are market share, Concentration Ratio for Biggest Four (CR4), Hirschman Herfindal Index (IHH), and Gini coefficient. The research results showed that there are 7 marketing channels with 3 to 4 marketing institutions in each channel. The largest market share is owned by 3 market players with sales of 90 kg/month each. The results of the four indicators analyzed from the red cayenne pepper market at Perumnas Way Halim Market indicated an oligopoly market structure. Market efficiency analyzed using indicators of market concentration, product differentiation, market entry and exit barriers and market information revealed a more efficient market structure.